Continuous decoupled redox electrochemical CO2 capture - Tao Liu; Yunpeng Wang; Yifan Wu; Wenchuan Jiang; Yuchao Deng; Qing Li; Cheng Lan; Zhiyu Zhao; Liangyu Zhu; Dongsheng Yang; Timothy Noël; Heping Xie (Nature Communications)
Abstract Electrochemical CO2 capture driven by renewable electricity holds significant potential for efficient decarbonization. However, the widespread adoption of this approach is currently limited by issues such as instability, discontinuity, high energy demand, and challenges in scaling up. In this study, we propose a scalable strategy that addresses these limitations by transforming the conventional single-step electrochemical redox reaction into a stepwise electrochemical-chemical redox process. Specifically, the hydrogen evolution reaction (HER) at the cathode and the oxidation of a redox carrier at the anode are employed to modulate the pH of the electrolyte, thereby facilitating effective CO2 capture. By decoupling the electrochemical swing for CO2 capture from redox carrier regeneration in both temporal and spatial domains, this approach mitigates unwanted side reactions and enhances system stability. Our results demonstrate a stable CO2 capture process sustained for over 200 h, with a electrical work of 49.16 kJe mol-1 CO2 at a current density of 10 mA cm-2. Furthermore, a scaled-up system capable of producing approximately 0.4 kg of pure CO2 per day maintained stable operation for 72 h, highlighting the potential feasibility of this method for large-scale decarbonization applications.